Pediatric Patient With a Giant Vertebrobasilar Dissecting Aneurysm Successfully Treated With Three Pipeline Embolization Devices - Jia, Luqiong; Wang, Jiejun; Zhang, Longhui; Zhang, Yunfeng; You, Wei; Yang, Xinjian; Lv, Ming (Frontiers in Neurology, 2020)
Pediatric intracranial dissecting aneurysms are rare, and treating this type of aneurysm in the vertebrobasilar circulation is more difficult. As an off-label application, pipeline embolization devices (PEDs) for posterior circulation dissecting aneurysms are reported to have good therapeutic effect. However, studies have found that PEDs for large or giant vertebrobasilar dissecting aneurysms have a poor effect and are associated with disastrous consequences. PEDs are feasible for vertebrobasilar dissecting aneurysms.Because there are more perforating arteries in the basilar artery, it is more prudent to use PEDs in this artery. We report a case of a pediatric patient with a giant vertebrobasilar dissecting aneurysm successfully treated with three PEDs combined with right vertebral artery occlusion, without complications. The patient’s headache symptoms resolved fully 3 months after the procedure, and the aneurysm was completely healed and excellent reconstruction of the left vertebral artery was seen 4 months post-procedure, using digital subtraction angiography.